The politics of surviving : how women navigate domestic violence and its aftermath - Sweet, Paige L., 1987- (University of California Press, 2021)
"A trauma revolution is quietly sweeping social services in the United States. For women who have experienced domestic violence, proving that you are a "good victim" is no longer enough when navigating these institutions. Women must also show that they are recovering, as if domestic violence were a disease: they must show that they are transforming from "victims" into "survivors." Through archival research, life story interviews, and participation observation, The Politics of Surviving shows that "becoming" a survivor is full of contradictions, perils, politics, and pleasures. Using an intersectional lens, Paige L. Sweet reveals how the idea of "resilience" and being a "survivor" can become a coercive force in women's lives. With nuance and compassion, The Politics of Surviving wrestles with questions about the gendered nature of the welfare state, the unintended consequences of feminist mobilizations for these programs, and the women who are left behind by the limited forms of citizenship we offer them"--